Pengembangan Model Konseling Kelompok Islami Dalam Menangani Krisis Spiritual Remaja Di Era Digital: Studi Pada Pembelajaran Pendidikan Agama Islam - Amiruddin Z Nur; Apriani Apriani; Ibnu Hajar; Abdul Rahman; Ria Rezky Amir (Journal of Innovative and Creativity, 2025)
This study aims to develop an effective Islamic group counseling model to address adolescent spiritual crises in the digital era, particularly within the context of Islamic Religious Education (IRE) learning. The digitalization era has brought significant impacts on adolescent spiritual life, creating new challenges such as religious identity crisis, spiritual distraction, and disorientation of Islamic values. This research employs a Research and Development (R&D) approach with a mixed-method design, involving 180 high school students in Makassar City as research subjects. Data were collected through observation, in-depth interviews, Likert scale questionnaires, and focus group discussions (FGD). The developed Islamic group counseling model integrates modern psychological approaches with Islamic spiritual values, encompassing stages: (1) spiritual problem identification, (2) homogeneous group formation, (3) implementation of Quranic and Hadith-based Islamic counseling techniques, (4) spiritual evaluation and reflection. Results show that the Islamic group counseling model effectively enhances adolescent spiritual resilience with pre-test scores of 2.3 increasing to 4.2 in post-test (p<0.05). This model successfully reduced spiritual anxiety levels by 67%, increased worship practices by 73%, and strengthened religious identity by 81%. These findings indicate that integrating Islamic group counseling in IRE learning can be an effective solution to address adolescent spiritual crises in the digital era. The research implications highlight the importance of developing IRE teachers' competencies as Islamic counselors and the need for IRE curricula responsive to digitalization challenges.